Nuevas tendencias en la investigación de la Inteligencia Emocional - Fernández Berrocal, Pablo; español; Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Megías-Robles, Alberto (Escritos de Psicología - Psychological Writings, 2022)
This monograph has been to publish studies that help us identify new trends in emotional intelligence research and advance in its conceptualization, measurement, and training from different disciplines such as neuroscience, psychology, and education. Specifically, this monograph has been organized to appear in two volumes of Escritos de Psicología - Psychology Writings corresponding to the years 2022 and 2023. Four articles have been published in this 2022 volume. The first two are systematic reviews; the first focused on the implications of emotional intelligence in the clinical, occupational, and educational context, and the second on the most used instruments for the measurement of emotional intelligence in Argentine adults. The other two articles are empirical studies focused on the educational field that analyze the Emotional Commitment of Teachers and its relationship with different psychoeducational variables, and how Emotional Intelligence is a protective factor of burnout in teachers. The four articles that make up this first part of the monograph coincide in highlighting the relevance of research in the assessment and training of Emotional Intelligence for its impact on our personal and professional lives.